Pendampingan Biopori kepada Masyarakat Desa Sarwodadi - Putra, Dhivangga A’raf Perdana; Rhamadhani, Atikah Jihan; Salsabila, Arifa; Cahyani, Sekar Sari Legita; Zenobia, Laksita Darda Hazza; Ramadhan, Fharaz; Safira, Intan Azzahra; Alfadhilah, Hilma Fahrezy; Mubarok, Muhammad Irfan; Prasetyo, Syahrul Dony; Nurdianto, Talqis (Universitas Muhammadiyah Yogyakarta, 2025)
The Empowerment Program uses a method of mentoring the creation and utilization of biopores as a solution to organic waste from community kitchens. This program is implemented in four main stages, namely socialization, action, benefits and sustainability. Based on the results of observations, three main problems were found: first, there is no well-integrated organic waste management system; second, there has been no massive dissemination of information about activities in the Village or in the world of education; third, the large number of agricultural areas with limited adequate fertilizers causes some soils to appear less fertile. From the results of the data collection, it is known that problems related to sustainable waste management are the most concerning to the community. This is due to residents who do not receive training and socialization of sustainable waste cultivation. The research method used is qualitative descriptive with a case study approach. At the socialization stage, the Regular Real Work Lecture (KKN) group 088 conducted counseling and interaction with residents in RT 01 regarding the importance of a healthy kitchen and a healthy environment. The main purpose of the socialization is to increase the insight of residents before taking action to make biopores. The next stage is action where residents practice together making biopores that function to produce benefits for plants in agricultural areas and. In addition, this program aims to create a sustainable program with a circular system, namely an economic concept that aims to minimize waste and garbage, and maximize the use of resources. The results of the program show that sustainable waste management through biopore optimization can increase awareness of the Sarwodadi Village community regarding environmental and kitchen health. In addition, this program has also succeeded in increasing concern both at the local and regional levels. This success can be the basis for further service with a focus on integrating waste in the context of broader and more sustainable organic waste management. There are 32 Family Groups that have utilized kitchen waste in the form of biopores. Thus, this circular waste management system is expected to be a model for the development of other villages that have similar problems